2018
DOI: 10.1002/ca.23018
|View full text |Cite
|
Sign up to set email alerts
|

The anatomy of free fibula osteoseptocutaneous flap in neophalloplasty in transgender surgery

Abstract: The Free Fibula Osteoseptocutaneous flap is a reliable option when used in neophalloplastic procedures. It possesses intrinsic rigidity that is sufficient for penetrative intercourse, and satisfactory sensation. We review the pros and cons of this procedure, as well the anatomy and surgical steps involved. Surgical text descriptions were enhanced by the creation of new anatomic illustrations. Anatomy of the donor and recipient sites, as well as the surgical technique leading to creation of the neophallus are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 15 publications
0
13
0
1
Order By: Relevance
“…Since the skin of the fibular flap is somewhat stiff and not free to be rolled on itself to create the neourethra, some authors have proposed to prelaminate the neourethra with STSG 6 months prior to the FOFF (71)(72)(73)(74). Donor site scarring is much reduced compared to other flap options, and can be easily covered by a sock or long trousers (75).…”
Section: Foffmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the skin of the fibular flap is somewhat stiff and not free to be rolled on itself to create the neourethra, some authors have proposed to prelaminate the neourethra with STSG 6 months prior to the FOFF (71)(72)(73)(74). Donor site scarring is much reduced compared to other flap options, and can be easily covered by a sock or long trousers (75).…”
Section: Foffmentioning
confidence: 99%
“…Similarly, the LSCN is coapted to one dorsal nerves of the clitoris. Since LSCN and clitoral nerves coaption often results in poor erogenous phallic sensation, it is highly suggested that the contralateral clitoral nerve should be preserved (70)(71)(72)75). The donor site is covered by full-thickness skin graft (74).…”
Section: Surgical Steps and Outcomesmentioning
confidence: 99%
“…A free osteofasciocutaneous fibula flap was also presented by Sadove et al (). With this technique, the number of required procedures and complications were fewer than with the radial forearm flap (Zaheer et al ). It offered several advantages for cisgender males who suffered traumatic amputations, as well as for female‐to‐male transgender individuals.…”
Section: Evolution Of Female‐to‐male Transgender Genital Reconstructionmentioning
confidence: 99%
“…This has ushered in the current era of phalloplasty for the treatment of gender dysphoria, where the focus is on achieving the best possible phallus reconstruction while minimizing overall morbidity. While many donor sites have been explored and are still currently utilized, the radial forearm and the anterolateral thigh are the most commonly used in phalloplasty surgery for gender dysphoria [6][7][8][9] [Figures 1 and 2]. Current techniques and surgical staging vary widely between institutions and individual surgeons, thus making it difficult to draw conclusions regarding the frequency and extent of complications.…”
Section: Introductionmentioning
confidence: 99%